2,3,4-Trihydroxy-benzaldehyde. - Ng, Seik Weng (International Union of Crystallography, 2008)
The title compound, C(7)H(6)O(4), crystallizes with two independent mol-ecules in the asymmetric unit. In both mol-ecules, the 2-hydr-oxy group is bound via intra-molecular hydrogen bonds to the aldehyde group. The mol-ecules inter-act through O-H⋯O hydrogen bonds to form a three-dimensional network structure; each hydr-oxy group serves as a donor to only one acceptor atom.